1990
DOI: 10.1136/pgmj.66.779.747
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery stenoses and thrombosis secondary to cavernous sinus thromboses in Fusobacterium necrophorum meningitis

Abstract: Summary: We report the case of a young man with Fusobacterium necrophorum meningitis who developed bilateral carotid artery stenosis associated with thrombosis of the cavernous sinuses.Intraluminal clot was present in the region of the stenoses for which he was anticoagulated. The clinical presentation, problems with diagnosis, the use of anticoagulation and the need for prolonged treatment with metronidazole are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
3

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 12 publications
1
36
0
3
Order By: Relevance
“…Bacterial sepsis (etiology unspecified) was identified as a risk factor in 4% of these. Sinovenous thrombosis is a recognized complication of F. necrophorum infection (20,211,370). In the current literature review, 15/251 patients with F. necrophorum infection had venous sinus thrombophlebitis; these patients ranged in age from 11 months to 38 years, with a median age of 15 years.…”
Section: Sinus Thrombosismentioning
confidence: 99%
“…Bacterial sepsis (etiology unspecified) was identified as a risk factor in 4% of these. Sinovenous thrombosis is a recognized complication of F. necrophorum infection (20,211,370). In the current literature review, 15/251 patients with F. necrophorum infection had venous sinus thrombophlebitis; these patients ranged in age from 11 months to 38 years, with a median age of 15 years.…”
Section: Sinus Thrombosismentioning
confidence: 99%
“…Other studies report harm from anticoagulation (15,19). Involvement of the cavernous sinus is generally regarded as an indication for anticoagulation (9,17). One review found that the use of intravenous heparin, followed by 3 months of warfarin, reduced morbidity among survivors (12).…”
Section: Case Reportmentioning
confidence: 99%
“…This is usually pharyngeal or tonsillar but foci in the face, ears, sinuses, mastoid and teeth have also been described (Hagelskjaer Kristensen & Prag, 2000). In addition there are reports of F. necrophorum meningitis complicated by thrombosis of the cerebral veins (Larsen et al, 1997) or cavernous sinus (Jones et al, 1990). Thrombosis is most probably due to the ability of F. necrophorum to cause platelet aggregation as has been demonstrated in vitro (Forrester et al, 1985;Kanoe et al 1989).…”
Section: Discussionmentioning
confidence: 99%